2019
DOI: 10.21614/chirurgia.114.2.222
|View full text |Cite
|
Sign up to set email alerts
|

Cytoreductive Surgery and Hyperthermic Intraperitoneal Chemotherapy for the Treatment of Peritoneal Carcinomatosis: Our Initial Experience

Abstract: RezumatIntroducere: Carcinomatoza peritoneală reprezintă un stadiu avansat al cancerelor abdominale în general şi a cancerului colorectal în particular. Singurele metode de tratament disponibile la momentul actual pentru această patologie sunt chimioterapia sistemică (caracter paliativ) şi chirurgia citoreductivă (CR) asociată cu chimioterapie intraperitoneală hipertermică (HIPEC). După revizuirea literaturii şi a ghidurilor de specialitate, putem afirma că procedura CR+HIPEC trebuie luată în considerare în ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Fefermann [ 31 ] found a 7% incidence of leukopenia (defined as <2000/mm 3 ) in 242 patients treated with CRS and HIPEC with mitomycin C, with a median nadir on day 5 postoperatively, who had a significantly longer ICU stay with respect to patients who did not develop leukopenia (11 vs. 6 days, p < 0.05). Bartos et al [ 4 ] found that only 2 of the 50 patients included in their study (4%) developed leukopenia; they included patients with peritoneal carcinomatosis of different origin. Wong et al [ 32 ] found an incidence of 12.3% of leukopenia (defined as <4000/mm 3 ) in 220 patients treated with CRS and HIPEC, with a median duration of leukopenia of 1 day (1–3 days).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fefermann [ 31 ] found a 7% incidence of leukopenia (defined as <2000/mm 3 ) in 242 patients treated with CRS and HIPEC with mitomycin C, with a median nadir on day 5 postoperatively, who had a significantly longer ICU stay with respect to patients who did not develop leukopenia (11 vs. 6 days, p < 0.05). Bartos et al [ 4 ] found that only 2 of the 50 patients included in their study (4%) developed leukopenia; they included patients with peritoneal carcinomatosis of different origin. Wong et al [ 32 ] found an incidence of 12.3% of leukopenia (defined as <4000/mm 3 ) in 220 patients treated with CRS and HIPEC, with a median duration of leukopenia of 1 day (1–3 days).…”
Section: Discussionmentioning
confidence: 99%
“…Several postoperative complications have been described after CRS and HIPEC, related to surgery, hyperthermia, and/or chemotherapy. The described morbidity rates are 25% to 51%, and up to 21–30% patients develop severe postoperative complications, requiring surgical, endoscopic, or radiological reintervention or readmittance to the intensive care unit (ICU) [ 2 , 3 , 4 ]. The described mortality rate varies between 0 and 18% [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the low-grade subgroup, the appendiceal neoplasm epithelial cells were positioned in a single row and the mucin secretion was typically exuberant, whereas the cells in the high-grade group were belt-shaped, island, or cribriform-shaped with severe dysplasia. The secretory function of the columnar cells was severely damaged, which led to a decrease in mucus secretion ( 2 , 6 , 18 ). Moreover, the concentrated tumor mass resulted in liver scalloping and omental cake ( 19 , 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…The recommended treatment for PMP is cytoreductive s u r g e r y ( C R S ) p l u s h y p e r t h e r m i c i n t r a p e r i t o n e a l chemotherapy (HIPEC) (6). This combination treatment is undoubtedly the optimal strategy associated with improved clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, IPEC includes the regional administration of chemotherapy of cytotoxic drugs in a concentrated dose, providing a higher cytotoxic effect to peritoneal tumor cells and low systemic cytotoxicity via localized delivery due to the plasma-peritoneal barrier [7]. What is more, HIPEC is based on the fact that antineoplastic agents above 41 • C present selective cytotoxicity to tumor cells, and increased absorption and penetration of the tumor tissue [8]. However, PRODIGE 7, a phase III clinical trial, suggested that in patients with PM from CRC, HIPEC was associated with a higher rate of complications, without improving the OS, when compared to cytoreductive surgery alone.…”
Section: Introductionmentioning
confidence: 99%